Impact of thermal maturation of the upper cretaceous bituminous limestone of Attarat Um Ghudran central Jordan on calcareous nannofossil preservation - Alqudah, Mohammad (American Chemical Society, 2023)
Oil shale deposits of the Late Cretaceous from three boreholes in central Jordan were examined to assess the impact of thermal maturation on the content of nannofossils. Thermal activity has been shown to have a strong effect on organic matter content and composition but its effect on calcareous nannofossil assemblages remains inconclusive. This study aims to determine the impact of thermal maturation on nannofossil assemblages and to compare this to an estimated maturity level based on bulk geochemical analysis. Micropaleontological and geochemical analyses were conducted on 31 samples from three oil shale wells drilled in Attarat Um Ghudran central Jordan. Several types of nannofossil preservation have been recorded, including dissolution, overgrowth, and breakage. In the Jordan oil shale sections, nannofossils exhibit a variety of preservation types, with intense dissolution in the middle part of the study sections. The vast majority of the samples had high TOC enrichment, with 29 samples exceeding values of >10%. Kerogen recovery and quality from the oil shale are very good, with a predominance of fluorescent amorphous organic matter (AOM) and minor algal components. The low fluorescence preservation index (FPI), which is 1 in most of the samples, indicates that alteration occurred due to intense thermal activities in the study interval. The palynomorph and AOM fluorescence, ranging from a spore coloration index (SCI) of 3 to 5, suggest that the studied samples were approaching the oil window. A correlation between the nannofossil preservation and geochemical parameters shows a predominance of poorly preserved nannofossils along with high total organic carbon contents and an elevated hydrogen index (HI). We show that low FPI values and a higher level of maturity are associated with poor nannofossil preservation, suggesting that nannofossils, in conjunction with petrographic analysis of kerogen, could be used as a rapid screening technique for estimating levels of oil-shale maturity. The nature of the tectonism in the study area, including faulting and a metamorphosed zone, enhanced the maturity, which might explain why the nannofossils were so significantly affected.